The Significance of the Decision of the Sanitary Authority and the Judgment of the Administrative Court Regarding the Employee’s Occupational Disease in the Proceedings for Granting Social Insurance Benefits - Kuczyński, Tadeusz (Acta Universitatis Lodziensis. Folia Iuridica, 2025)
The subject of the article is the significance of the decision of the state sanitary inspector and the judgment of the administrative court on the employee’s occupational disease in the proceedings for granting social insurance benefits due in connection with such a disease. The proceedings related to occupational diseases include two spheres. The first is the administrative proceedings conducted by the state sanitary inspector ending with the issuance of a decision on the occupational disease, with the possibility of appealing it to the administrative court. The second is the proceedings before the Social Insurance Institution in order to issue a decision establishing the right to social insurance benefits due to the employee due to the effects of the occupational disease, with the possibility of appealing it to the labour and social insurance court. Referring to the views of the literature on the subject and court decisions on the analysed topic, the author reviews the presented positions, subjecting them to critical analysis.